Academic Advancement in Global Surgery: Appointment, Promotion, and Tenure. Issue 2 (February 2020) - Wren, Sherry M.; Balch, Charles M.; Doherty, Gerard M.; Finlayson, Samuel R.; Kauffman, Gordon L.; Kibbe, Melina R.; Haider, Adil H.; Minter, Rebecca M.; Mock, Charles; Muguti, Godfrey I.; Numann, Patricia J.; Olutoye, Oluyinka O.; et al.
Abstract : N/A: There is growing interest in global surgery among US academic surgical departments. As academic global surgery is a relatively new field, departments may have minimal experience in evaluation of faculty contributions and how they integrate into the existing academic paradigm for promotion and tenure. The American Surgical Association Working Group on Global Surgery has developed recommendations for promotion and tenure in global surgery, highlighting criteria that: (1) would be similar to usual promotion and tenure criteria (eg, publications); (2) would likely be undervalued in current criteria (eg, training, administrative roles, or other activities that are conducted at low- and middle-income partner institutions and promote the partnerships upon which other global surgery activities depend); and (3) should not be considered (eg, mission trips or other clinical work, if not otherwise linked to funding, training, research, or building partnerships).